2009
DOI: 10.1002/chin.200918063
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Adamantyl‐Containing Fluorinated 1,3‐Diketones

Abstract: Bridged compounds Q 0060Adamantyl-Containing Fluorinated 1,3-Diketones -[by reaction of fluorinated 1,3-diketones with 1,3-dehydroadamantane]. -(BUTOV*, G. M.; MOKHOV, V. M.; PARSHIN, G. Y.; KUNAEV, R. U.; SHEVELEV, S. A.; DALINGER, I. L.; VATSADZE, I. A.; Russ.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2009
2009
2009
2009

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…Possible biological activity of some adducts was analyzed using Mikrokosm software. It was found that compounds III and VIIb may be interesting as potential drugs [4] possessing analgesic, narcotic, and cardiotonic activity.…”
mentioning
confidence: 99%
“…Possible biological activity of some adducts was analyzed using Mikrokosm software. It was found that compounds III and VIIb may be interesting as potential drugs [4] possessing analgesic, narcotic, and cardiotonic activity.…”
mentioning
confidence: 99%